Adoption and Impact of Mobile Wallets and Digital Banking in Nepal - Acharya, Pravesh (BMC Research Journal, 2026)
From the beginning of 2020, digital financial services (DFS) in Nepal have evolved from a non-essential items tool kit to an essential daily habit, largely due to the improving reach of the smart phone devices with people post pandemic change of behavior from cash payments to cashless payment and most importantly regulatory requirements by NRB. The research design for this study is descriptive and analytical based on quantitative approaches . This article will apply case study approach on national digital payments trends, progresses achieved, and system developments up to 2025. The major results highlights a big growth in the banking ecosystem, with the mobile channel leading in large transactions (USD 2.70bn) and digital wallets leading charge in retail micro transactions (USD 0.26bn). The quick changes has, however, brought in significant structural problems from app crashes, to a rise in cyber fraud reported cases by multiple than before. However several number of structural issues have arisen including app crashes and glitches and a doubling of cyber fraud cases. Its concluded in this article that, although digitalisation helps to reduce the transaction transparency and financial inclusion in remote areas, the sustainability of such ecosystems requires strong and effective policy changes, 24x7 functioning cyber security architectures, and targeted campaigns in financial literacy in rural areas.